Innovation in Waste Bank Management Through Business Model Canvas and Social Entrepreneurship Approach - Wulandari, Maria Sri; Nurasti, Cicilia; Gopito, Florensia Eka; Siti, Kristina; Sumarwan SJ, Antonius (PT Mattawang Mediatama Solution, 2025)
This study aims to develop an innovative school waste bank model based on social entrepreneurship using the Business Model Canvas (BMC) framework to increase student and community participation in sustainable waste management. A descriptive qualitative approach with a case study strategy was conducted at SMK Strada II, West Jakarta. Data were collected through in-depth interviews, observation, document analysis, and focus group discussions. The results show that integrating BMC elements such as key partners, value propositions, and revenue streams strengthens the program's structure and sustainability. Active involvement of students and the surrounding community enhances its educational, social, and economic functions. Simple incentives and collaborative approaches effectively raise environmental awareness. This study is limited to one school and has not measured long-term impacts. The findings offer opportunities to replicate the model in other schools and encourage educational policies based on social entrepreneurship and environmental education.